"Dior and I": understanding the combination of creativity and economy in fashion industry. Issue 3 (9th October 2017) - Leclair, Margot
Abstract : Purpose: Fashion documentaries are many. Although their behind-the-scene access presents some undeniable interest, the author suggests that while revealing information about the creative process, the economic priorities are understated. Design/methodology/approach: The author reviews Frederic Tcheng's Dior and I documentary, which brings the viewer inside the storied world of the Christian Dior fashion house with a look at the creation of Raf Simons' first haute couture collection as its new artistic director. Findings: The author analyses the documentary with the literature on tensions between creativity and economy to bring some light into the observed frictions. Digging deeper, the literature is also used to reveal several issues that are overlooked in the documentary, small glimpse of the organization. Originality/value: The paper voices what is easily silenced around creative work in the fashion industry, as well as and more globally in creative industries.